An exploration of inquiry-based authentic learning enabled by mobile technology for primary science. (14th October 2020) - Yeung, Wing Kei; Sun, Daner
The rapid development of mobile technologies has been shown to assist in science learning, but more research is needed on the pedagogical integration of such technologies into authentic learning in a formal science curriculum. Thus, we conducted a study on exploring the impact of a learning platform nQuire-it together with its scientific mobile sensors in an authentic and inquiry-based learning environment on students' science learning. To examine the effectiveness of this learning platform and its mobile sensors, a mixed methods study was conducted for analysing students' performance in science inquiry, conceptual understanding and ability to connect content knowledge with daily life experiences. The results suggested that the learning platform together with scientific mobile sensors supported students' authentic science learning in following dimensions: academic performance, learning motivation, interest in learning and ability to link knowledge gained in and outside the classroom.